A highly sensitive turn-on ratiometric luminescent probe based on postsynthetic modification of Tb3+@Cu-MOF for H2S detection. Issue 38 (19th September 2017) - Zheng, Xubin; Fan, Ruiqing; Song, Yang; Wang, Ani; Xing, Kai; Du, Xi; Wang, Ping; Yang, Yulin
Abstract : A novel probe, designed and prepared through PSM of Cu-MOFs and Tb 3+ ions, shows high sensitivity and selectivity for H2 S. Abstract : The fabrication of luminescent materials with lanthanide cations encapsulated within MOF pores is currently of interest because luminescent materials are used in numerous applications. In this study, a distinctive strategy via postsynthetic modification (PSM) of a novel metal–organic framework [Cu(HCPOC)2 ] n (Cu1 ) (H2 CPOC = 5-(4′-carboxyphenoxy)nicotinic acid) and terbium ions (Tb 3+ ) for sensing hydrogen sulfide (H2 S) is reported. The obtained compositeTb 3+ @Cu1 emits a weak typical Tb 3+ ion emission and strong ligand-centred emission. Interestingly, H2 S, as a strong electron donor, can strongly enhance the luminescence of Tb 3+ through its superior affinity for Cu 2+ ions. The compositeTb 3+ @Cu1 was designed as a luminescent turn-on ratiometric probe for H2 S detection, showing high sensitivity and selectivity. The detection limit ofTb 3+ @Cu1 (1.20 μM) is far below that ofCu1 (13.25 μM). Moreover, a similar ligand, 5-(4′-carboxyphenyl)nicotinic acid (H2 CPC), was used to synthesize a fascinating structure, [Cu5 (CPC)2 (HCPC)2 (OH − )4 ] n (Cu2 ), which was quite similar to that of the famous semiconductor MoS2, with the advantageous support of an organic linker between layers, and it showed a band gap of 2.45 eV.